The Effect of Edutainment Learning Methods on Fifth-Grade Students’ Learning Outcomes in Theme 8 of Our Friend Environment - Eanassyalili Jasika Siregar; Patri Janson Silaban; Candra Ronitua Gultom; Bogor Lumban Raja; Rumiris Lumban Gaol (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper presents the effect of using the Edutainment learning method on students’ learning outcomes on theme 8 of our friend environment in class V at SD Negeri 068006 Simalingkar in the academic year 2022/2023. The research uses quantitative methods. The research population was 245 students from all grades I–VI at SD Negeri 068006 Simalingkar. Sampling uses a purposive sample and the sample used involved 30 fifth-grade students. The research results indicate that students’ learning outcomes using the Edutainment learning method are included in the very good category with an average score of 81.86 with a correlation test result of 0.634, which means rcount (0.634) ≥ rtable (0.361), thus Ha is accepted. Therefore, there is a considerable effect between the use of the Edutainment learning method and students’ learning outcomes in class V at SD Negeri 068006 Simalingkar. It can be seen from the research results of the T-test, where rcount 4.335 ≥ rtable 2.048, Ha is also accepted. It implies that there is a significant positive effect from the use of the Edutainment learning method on students’ learning outcomes in theme 8 of our friend environment in class V at SD Negeri 068006 Simalingkar in the academic year 2022/2023.